Rancang Bangun Converter Kit LPG (Liquefied Petroleum Gas) Pada Mobil Minimalis Roda Tiga - Mohammad Jauhar Firdaus; George Endri Kusuma; Tri Andi Setiawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
The most widely used means of transportation for Indonesians are motorized vehicleswhose numbers will rise every year. Increasing the number of motor vehicles also affects the increasein the amount of fuel consumption used. The solution offered is the conversion of fuel oil to gas fuel inmotor vehicles as an alternative fuel. So that the Converter Kit of BBM to LPG is needed which iseasier to obtained than other gas fuels.This research produce Converter Kit LPG which make someconcept, then chosen one to make the product. Testing is done by installing Converter kit on theengine of a three-wheeled minimalist car and tested the dynotest and fuel consumption.Obtained theperformance of LPG fuel engine with torque and maximum power at 6500 RPM of 15.2 Nm and 12.79Hp. Fuel consumption is 1 kg in a distance of 30 km or equivalent to Rp 188.89 per km.